An experimental study on effect of curvatures of upstream tube on thermal performance of downstream tube in cross-flow of air - Kunal; Sushil Kumar Dhiman (Scientific Reports)
Abstract Heat transfer on a straight tube in the wake of a tube of same diameter with different curvatures was investigated in cross-flow of air at Reynolds number of 35,000. The straight tube was given constant heat flux condition and placed at different spacing ratios of 2.0, 2.25, 2.5, 3.0, 3.5, and 4.0, from the curved tubes at blockage ratio of 0.1. Four different curvatures ratios 0.5, 1.0, 1.5 and 2.0, on curved tubes were given which were aligned with the mainstream as concave and convex profiles forming different combinations of curvature ratios and spacing ratios to analyse their thermal performance. The study shows a paramount advantage of enhanced thermal performance using curved tube combinations over straight tube combinations and identifies a Reynolds number-based inflection point describing “Heat Promoter” as upstream segment of the tube. The results illustrate that concave curved combination with curvature ratio 1.0 at spacing ratio 2.5 exhibited highest thermal performance with 2.36 times enhanced heat transfer.